Pengaruh Terapi Slow Stroke Back Massage (SSBM) Terhadap Perubahan Tekanan Darah Pada Pasien Stroke Non Hemoragik Di Ruang Melati 4 RSUP. Dr. Soeradji Tirtonegoro Klaten - Sekar Pinasthika ((JKG) Jurnal Keperawatan Global, 2018)
Background. Almost 50% of stroke caused by blood pressure increase. Management Non-Haemorrhagic Stroke patients in non-critical phase to lowering blood pressure can be done with non-pharmacologic therapy and pharmacologic therapy. Slow Stroke Back Massage is one of the non-pharmacological therapy relaxations which can lower blood pressure. The purpose of this research is to 1) Determine the effect of slow stroke back massage therapy to changes in blood pressure in patients with non-hemorrhagic stroke. 2) To describe characteristics of patients with non-hemorrhagic stroke 3) Determine the change in blood pressure in patients with non-hemorrhagic stroke before and after the slow-stroke back massage therapy. Methods. Type of this research is quasi-experiment with the design of One Group Pretest-Posttest Design. The Results. The result of this research is their influence of Slow Stroke Back Massage therapy to changes in blood pressure in patients with non-hemorrhagic stroke in Melati 4. This is evidenced by the results of the Wilcoxon test analysis where the systolic blood pressure before and after therapy SSBM ρ = 0.000 and a significance value of diastolic blood pressure before and after therapy SSBM ρ = 0.003. Because the value of ρ <0.05, then Ho is rejected and Ha accepted, Conclusion. There is the influence of Slow Stroke Back Massage therapy to changes in blood pressure in patients with non-hemorrhagic stroke in Melati 4 Dr. Soeradji Tirtonegoro, Klaten General Hospital.